2014
DOI: 10.1103/physrevb.90.235308
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetometry studies of spin dynamics in quantum Hall systems

Abstract: We performed a nuclear magnetometry study on quantum Hall ferromagnet with a bilayer total filling factor of ν tot = 2. We found not only a rapid nuclear relaxation but also a sudden change in the nuclear spin polarization distribution after a onesecond interaction with a canted antiferromagnetic phase. We discuss the possibility of observing cooperative phenomena coming from nuclear spin ensemble triggered by hyperfine interaction in quantum Hall system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…One possible realization is with a nuclear spin ensemble in GaAs semiconductors coupled with the NG mode as a low-frequency electron spin fluctuation [20,21]. Here the spin dynamics in quantum dots and the quantum Hall regime has been extensively investigated [13,[25][26][27].…”
mentioning
confidence: 99%
“…One possible realization is with a nuclear spin ensemble in GaAs semiconductors coupled with the NG mode as a low-frequency electron spin fluctuation [20,21]. Here the spin dynamics in quantum dots and the quantum Hall regime has been extensively investigated [13,[25][26][27].…”
mentioning
confidence: 99%
“…The candidate hybrid quantum systems to observe these phenomena are, one is the GaAs semiconductor where nuclear spins are coupling to the electron spins in the QH state through the hyperfine interaction. When we initially prepared the nuclear double spin domain having antiparallel configuration induced by the DNP [22,23], by tuning the QH state so that the linear dispersing NG mode as the bosonic reservoir emerge [24][25][26], we observe our collective phenomena. The second candidate is the electron spin ensemble in the NV center in diamonds coupling to the superconducting resonator [27].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the nuclear-spin relaxation time in the CAF phase is the shortest compared with those in the other two phases (the ferromagnetic phase and the spin-singlet phase). More recent experiment [12], where the spatial nuclear-spin polarization distribution was recorded after the exposure to the CAF phase, showed a sudden change in the nuclear-spin polarization distribution from the initial one. These experimental results suggest a unique many-body interaction between electron and nuclear spin systems.…”
Section: Introductionmentioning
confidence: 94%
“…The above situation may change when the nuclear spins interact coherently with low-energy excitation modes of electron spins such as Nambu-Goldstone (NG) modes. For instance, the NG modes appear in the canted antiferromagnetic (CAF) phase [4][5][6][7][8][9][10][11][12] due to the spontaneous breaking of the rotational U(1) symmetry. This phase is the most interesting one among the three phases of the total filling factor 2 n = bilayer QH systems: the ferromagnetic phase, the spin-singlet phase and the CAF phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation